Otimização de tráfego de rede de computadores de uma empresa de pequeno porte com o uso do spanning-tree protocol - SILVA, Ivone Cléa Alves da (2023)
With the expansion of organizations and their computer networks, the high availability of the computer network is a requirement. Even short periods of network downtime can generate productivity gains. Therefore, the present work presents a proposal to optimize the traffic of the computer network of a fictitious small company, through the implementation of redundancies and a subsequent implementation of the Spanning Tree Protocol (STP) technique, a protocol defined by the IEEE (Institute of Electrial and Electronic Engineers) 802.1D. It works at the level of protocol 2 of an OSI (Open Systems) protocol model (Open Systems) and aims at the performance of redundant connections, offering the best performance of a network. With a simulation of S, we seek to present the protocol and its application in a network as a data traffic protection device, its benefits and possible possibilities of using this protocol in Ethernet networks.